(untitled) (Journal of Medical & Health Sciences Review, 2025)
Objective: To identify and analyze the factors influencing nurses’ compliance with standard precautions, providing insight for targeted interventions and improved adherence. Material and Methods: Forty-five Registered Nurses fulfilling the inclusion criteria were enrolled in study from Nishtar hospital Multan. A total of professional nurses from various departments at public hospital were present atthetimethedata wascollected. As a result, the majority of participants were the nurses who would have jobs at this public hospital ona permanent basis. TheData was analyzedthroughsoftware SPSS - 25. Results: Mean age of our study cases was 39.22 ± 8.73 years (Range; 25 years to 58 years) while 57.8 % (n=26) were aged up to 40 years. Factors responsible for compliance, protection of patient and self comes first and patients’ education about benefits of PPEs, 95.6 % (n = 43). Regarding, protection from being exposed to germs after usage of standard precautions, 95.6% (n=43) reported yes and 4.4 % (n=2) reported otherwise. Regarding positive role in not being the carrier of infection satisfies you, 93.3% (n=42) reported Yes while remaining 6.7 % reported No. Forty three (95.6 %) of these nurses agreed that Previous exposure to micro-organisms makes them concern with usage of SP and all of them (100%) agreed that Continuous reminders and continuous education are necessary for SP guidelines. Forty (88.9%) of these study participants reported that Patients personal look and hygienic condition was also acause of following SPs. Thirty-six (80.0 %) of our study participants also agreed that Education level of patient is also main cause to use SPs and all of them (100 %) described that Act of following the standard precautions by senior colleagues and doctors urges them to use the same SPs. Forty-one (91.1 %) of these nurses also reported that Fear of infecting their family makes them conscious to use SPs and Pressure fromseniors is also a cause of following the guidelines of SPs was also reported by all (100%) these study participants. Equipment not in easy access or locked was reported by 75.6 % (n = 34) while 88.9 % (n = 40) reported activities of patient care were not carried properly as venipuncture was difficult with gloves and all of them reported that use of gloves irritated their skin. Forty-three (95.6 %) reported Multiple responsibilities and work load prohibits them to use SPs andall45 study participants reported Patients discomfort with their use of SPs. Six (13.3 %) reported Usage of masks and gloves destroys their looks while all of them (100%) reported shortage of nursing staff was also main cause of non-compliance with standard precautions. Forty (88.9%) reported Nursing care to children with gloves and mask made them uneasy and all of them (100%) reported lack of PPEs and poor fitting of PPEs. Conclusion: Lack of easy access to the equipment, shortage of nursing staff, multiple responsibilities & workload and poor fitting of the personal protective equipment were the main factors affecting nurses’ compliance with infection prevention. Overall, nurses’ compliance was good along with good knowledge and practices. Local Governments should take measures to overcome shortage of nurses and equipment to share burden of work. This will improve further the compliance of nurses which will, in turn ensure patient safety and effective infection prevention program. This will decrease prolonged hospital stays due to nosocomial infections and decrease extra-healthcare expenditures.